A new method to sort differentiating osteoclasts into defined homogeneous subgroups - Hulley, PA; Knowles, HJ (MDPI, 2022)
Osteoclasts regulate skeletal development but also drive pathological osteolysis, making them prime therapeutic targets. Osteoclast research is limited by the heterogeneity of osteoclast populations generated in vitro, where the mixture of undifferentiated monocytes, binuclear pre-osteoclasts and multinucleated osteoclasts has by necessity been considered a single osteoclast population. This study describes the differentiation of primary human CD14+ monocyte-derived osteoclasts in 3D collagen gels. These osteoclasts remained small (>95% with ≤5 nuclei) but were viable and active; when released from the gel with collagenase, they fused rapidly when reseeded onto solid substrates and resorbed dentine for 2–3 weeks. 3D-generated osteoclasts expressed cell surface markers of osteoclast differentiation (e.g., CD9, RANK, OSCAR, CD63, CD51/61) which, with their small size, enabled live cell sorting of highly enriched viable subpopulations of human osteoclasts that retained full functional resorption capacity. Low-yield osteoclast preparations were strongly enriched to remove undifferentiated cells (e.g., 13.3% CD51/61+ to 84.2% CD51/61+), and subpopulations of CD9+CD51/61− early osteoclasts and CD9+CD51/61+ mature cells were distinguished. This novel approach allows the study of selected populations of differentiating osteoclasts in vitro and opens the door to in-depth transcriptomic and proteomic analysis of these cells, increasing our ability to study human osteoclast molecular mechanisms relevant to development, aging and disease.